2022
DOI: 10.18502/ijph.v51i8.10271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Animal Fasciola Spp. Isolates from Lorestan Province, Western Iran

Abstract: Background: We aimed to detect the genetic diversity of samples identified morphologically as Fasciola spp. from sheep, cattle and goat from Lorestan Province, western Iran using PCR-RFLP method. Besides, we evaluated the genetic diversity indices, sequencing and phylogenetic analysis using mitochondrial gene (ND1 and CO1). Methods: PCR-RFLP analysis of ribosomal ITS1 fragment by RsaI restriction enzyme to investigate the genetic characteristics of Fasciola species obtained from different hosts (18 sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The highest prevalence rate of fascioliasis in animals is reported in the north, and the lowest prevalence is in Central Iran [20]. Heydarian et al [21] investigated the seroprevalence of human fascioliasis in Lorestan Province, Western Iran, on 1256 humans. They detected anti-Fasciola antibodies in 16 individuals (1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence rate of fascioliasis in animals is reported in the north, and the lowest prevalence is in Central Iran [20]. Heydarian et al [21] investigated the seroprevalence of human fascioliasis in Lorestan Province, Western Iran, on 1256 humans. They detected anti-Fasciola antibodies in 16 individuals (1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of F. hepatica and F. gigantica can generally be used for distinguishing between them, but for detecting and distinguishing intermediate forms between Fasciola species, one need to use molecular methods, and genetic markers (20). Aryaeipour et al (31) concluded that the PCR-RFLP method was a more reliable method than morphology for the differentiation of Fasciola species and the morphological methods were inefficient for determining genetic diversity. The first and the second internal transcribed spacers (ITS1 and ITS2) of the nuclear ribosomal DNA (rDNA) were used as genetic markers for genetic characterization and differential between the species of Fasciola that have been confirmed by several previous studies (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…These markers are non-coding regions between the 18S, 5.8S, and 28S coding regions and have been used for diagnostic purposes at the species level (35)(36)(37)(38). In the Middle East, many studies relied on the ITS1 marker to identify Fasciola species (39,40). In this research, Fasciola spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several markers have been developed and used to assess the population structure of Fasciola species such as the ribosomal internal transcribed spacer (ITS), phosphoenolpyruvate carboxykinase (Pepck), DNA polymerase delta (Pold), cytochrome c oxidase I (COI) and the NADH dehydrogenase (ND) genes (Bozorgomid et al, 2020;Heydarian et al, 2022;Kasahara et al, 2021;Shafiei et al, 2014). It has been reported that the genetic diversity of this parasite may have a role in drug resistance, virulence, pathogenicity, clinical characteristics of the disease and certain epidemiological features (Lalor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…F. hepatica and F. gigantica can generally be distinguished on the basis of morphological criteria but the existence of parthenogenic (aspermic) Fasciola flukes with intermediate morphological characteristics between the two species can cause confusion (Aryaeipour et al., 2017 ). Several markers have been developed and used to assess the population structure of Fasciola species such as the ribosomal internal transcribed spacer (ITS), phosphoenolpyruvate carboxykinase ( Pepck ), DNA polymerase delta ( Pold ), cytochrome c oxidase I ( COI ) and the NADH dehydrogenase ( ND ) genes (Bozorgomid et al., 2020 ; Heydarian et al., 2022 ; Kasahara et al., 2021 ; Shafiei et al., 2014 ). It has been reported that the genetic diversity of this parasite may have a role in drug resistance, virulence, pathogenicity, clinical characteristics of the disease and certain epidemiological features (Lalor et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%